Perception of Neurosurgical Residents about Learning in Operation Theatre in Tertiary Care Hospitals - Sohail Amir; Brekhna Jamil; Usman Mehboob; Shahid Ayub (Gandhara University, 2023)
OBJECTIVES To explore Neurosurgical postgraduate residents perceptions of their learning environment in operating rooms. METHODOLOGY From March 2022 to August 2022, this cross-sectional study will be carried out in the Department of Neurosurgery Hayatabad Medical Complex, Peshawar, Lady Reading Hospital Peshawar, and Ayub Teaching Hospital Abbottabad. The STEEM survey examined how surgical theatres were perceived as educational environments. After receiving informed consent, a printed questionnaire was provided to 32 surgical residents. SPSS 24 was used to conduct descriptive and inferential data analyses. RESULTS Thirty-one (31) of the 32 surgical residents that were surveyed (or 98.3%) answered. Residents' average age was 29.27 years (2.37); 27 were male, and 05 were female. Most residents were in their third (34.4%) and fourth (21.3%) years of residency. 147.66 (18.57) was the overall mean score. Participants' age and gender did not affect the mean scores; nevertheless, responses were statistically more favorable for residents in their first or fifth year of residency. Fifty-three locals responded favorably or positively overall. CONCLUSION Overall, residents had positive opinions of their training, their supervisors, the opportunities for learning in the operating room, the environment, and the monitoring they received.